PENGUATAN EKONOMI NASIONAL PASKA COVID 19 MELALUI LEMBAGA FILANTROPI ISLAM DI INDONESIA: TELAAH YURIDIS TERHADAP UU YANG BERKAITAN DENGAN FILANTROPI DAN 34 FATWA MUI - Fitriyanti, Yessi (Penerbit Lafadz Jaya, 2026)
This study aims to examine the strengthening of the national economy after the COVID-19 pandemic through the role of Islamic philanthropic institutions in Indonesia, using a juridical approach to related legal regulations and fatwas. The method used is a qualitative literature review, analyzing various laws and regulations related to philanthropy and 34 relevant fatwas from the Indonesian Ulema Council (MUI). The results indicate that Islamic philanthropic institutions have significant potential to support national economic recovery through the systematic and sharia-compliant management of zakat, infaq, and sedekah. However, challenges remain in harmonizing existing regulations and fatwas, as well as the need to strengthen the legal framework that supports the role of Islamic philanthropic institutions as effective socio-economic instruments. This study suggests the need for regulatory revisions and strengthened synergy between the government, religious institutions, and Islamic philanthropic institutions to optimize their contribution to national economic recovery.